Development of digital financial instruments and their use in the activities of entities of the pharmaceutical industry of Ukraine - Manoylenko, Oleksandr; Kuznetsova, Svitlana (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The pharmaceutical industry of Ukraine is an important component of its economy and the health of its population. At all stages of its development, it was and remains the centre of innovations, where the scientific and technological potential of the region is concentrated.Theoretical and practical aspects of the development of innovative digital financial instruments and financial support were investigated and on their basis the activities of enterprises of the pharmaceutical industry in the conditions of the digital economy and electronic commerce as the most perspective segment of the modern market in the conditions of restrictions on direct contacts and the movement of people due to measures to combat the pandemic have been studied, military actions and security of people have been studied. It was determined that financial instruments can be conditionally divided into traditional and digital. They have similar content, functions, and features, however, they have different spheres of manifestation, advantages, disadvantages, and risks. At the same time, the implementation of digital financial instruments allows to significantly save the time of entrepreneurs and customers or services; it also saves cash; simplifies administration and, as a result, it increases the profi tability of enterprises, in particular, the pharmaceutical industry. The study shows wide opportunities for the development and application of embedded finance in the pharmaceutical sphere with the aim of increasing business profitability by saving time, premises and other means of providing and implementing financial activities; and economic benefits to consumers and partners; optimization of business processes and management of activities in general; promotion of innovation, investment and integration processes.
Keywords: digital financial instruments; embedded finance; digital economy; pharmaceutical industry; business technologies; financial results